INVESTIGATION ON METAL OXIDES NANOMATERIALS FOR ENHANCED SURFACTANT FLOODING - CHAI, MUHAMMAD HANIF HIDAYAT (2020)
Energy is at high demand globally which leads to a need for further extraction of hydrocarbon. The conventional way of extracting hydrocarbon is no longer able to sustain the need for energy consumption hence arise the need for economic and environmental method for hydrocarbon recovery. In recent years, nanotechnology has been introduced widely in different sectors of oil and gas industries such as exploration, drilling and completion, flow assurance and production sectors. In this study, impedance of nanofluid is determined for electromagnetic propagation in porous medium. Then, colloidal stability of coated and pure nanomaterials was investigated, as well as the performance of selected nanomaterials was evaluated for enhanced oil recovery (EOR) application.